2014
DOI: 10.1590/0104-1169.3556.2476
|View full text |Cite
|
Sign up to set email alerts
|

The reasons of the nursing staff to notify adverse events

Abstract: OBJECTIVE: this research aimed to understand the motivation for reporting adverse events from the perspective of nursing staff in the work environment. METHOD: qualitative study that used the phenomenology of Alfred Schutz for reference, which offers a systematic approach to understand the social aspects of human action. Data were collected by open interviews with 17 nurses and 14 technicians/assistant nurses in a university hospital. RESULTS: motivation was revealed through six categories: all types of occurr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0
21

Year Published

2017
2017
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(40 citation statements)
references
References 14 publications
1
18
0
21
Order By: Relevance
“…Underreporting can occur due to several factors such as fear, guilt and the type of notification system, being one of the main difficulties of the voluntary notification method (13) . Other studies have also revealed the existence of fear in reporting facing the investigative and analytical process, because taking responsibility was followed by orientation or warning (25) . Thus, the existence of the punitive culture at the studied institution undermines notification and learning with error, considering that punishment is different from accountability.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Underreporting can occur due to several factors such as fear, guilt and the type of notification system, being one of the main difficulties of the voluntary notification method (13) . Other studies have also revealed the existence of fear in reporting facing the investigative and analytical process, because taking responsibility was followed by orientation or warning (25) . Thus, the existence of the punitive culture at the studied institution undermines notification and learning with error, considering that punishment is different from accountability.…”
Section: Discussionmentioning
confidence: 99%
“…Another aspect concerns the absence of analyzing the causes. Following the notification there are a series of interlinked actions: analyzing the event and the risk situation, directing learning aimed at improving the safety of patients during their hospitalization (25) . It is a systematic process that analyzes the factors that contribute to an incident, identified by reconstructing the sequence of events and by the constant questioning of its occurrence until its elucidation; a tool that needs to be better used to ensure patient safety, assisting in the actions to be taken to reduce and manage future damage (27) .…”
Section: Discussionmentioning
confidence: 99%
“…Em relação à segurança do paciente, a notificação dos eventos adversos torna-se um instrumento essencial, uma vez que propicia auxílio à gestão da assistência (15) . No presente estudo, percebeu-se que os enfermeiros conhecem o sistema de notificação e são os principais notificadores, entretanto, devem desempenhar melhor seu papel de líder da equipe, apoiando, disseminando e informando ações em prol da notificação bem como os resultados das análises das notificações.…”
Section: Discussionunclassified
“…O retorno sobre a notificação para o profissional é capaz de estabelecer um canal de comunicação que possibilita à instituição fornecer um parecer sobre sua conduta, orientação, informações sobre a estratégia para a resolução do problema e necessidade de reavaliação (15) . As discussões provenientes dos resultados de análises de EA podem servir como base para a tomada de decisão e para planejamento da segurança do paciente a partir da análise, monitoramento, minimização e prevenção de incidentes que possam causar EA (22) .…”
Section: Discussionunclassified
“…1 O erro ou incidente pode ser definido como o evento ou circunstância que poderia ter resultado, ou resultou em dano desnecessário ao paciente, podendo ser oriundo de atos intencionais ou não. Quando não atingem o paciente, ou são detectados antes, são denominados de near miss (quase erro), quando o atingem, mas não causam danos discerníveis, são denominados de incidente sem dano, e quando resultam em dano discernível, são nomeados de incidentes com dano ou EA.…”
Section: Introductionunclassified